Integrated Pest Management System with Impulsive Control of Spatial Heterogeneity (Journal of Partial Differential Equations, 2021)
An impulsive integrated pest management system with diffusion is investigated within this paper. The conditions for pest eradication of the impulsive system without natural enemies are established based on the Krein-Rutman theorem andthe comparison principle for parabolic equations. Integrated pest management can beachieved at an exponential rate, when the principal eigenvalues of the auxiliary systemis large enough. Numerical simulations are presented to demonstrate the theoreticalresults. A discussion is given at the end.
Keywords: Integrated pest management; eigenvalue problem; pest control; diffusion.